الأبعاد التربوية والفنية للأعمال الجماعية في الجداريات النحتية - Taha Hassan Massad alghabashi (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2023)
There are many types of arts and its branches and divisions based on human studies from its various philosophical, theoretical and applied aspects, and visual arts is one of the types of arts that depend in its awareness on the sense of sight from which it took its name. With the artist's interest in environmental aesthetics and environmental aesthetics, he was able to create aesthetic and creative murals with the aim of raising the visual perception of the environment, not with fixed concepts or methods and trends of plastic art.Fine artists seek to develop collective behavior and raise public taste through murals through a visual form. Sculpting of open spaces appeared when artists’ preoccupation with contemporary modern art doctrines led to the confinement of fine art production within museums and galleries, which in turn affected the public taste of community members."The choice of the topic between the one who teaches and the working group, depends on their interests, experiences and abilities, and he brings it up to the topic and discusses it with them, and chooses the appropriate materials and techniques for implementation, and the topic is exciting to achieve the aesthetic idea. Therefore, the return always has many dimensions from group work,